ERP und SCM Enterprise Resource Planning und Supply Chain Management in der Industrie - Kurbel, Karl 1947- (De Gruyter Studium, 2021)
Enterprise Resource Planning (ERP) and Supply Chain Management (SCM) are key areas of activity in all industrial companies. This new edition covers a range of topics, from the fundamentals and implementation of ERP and SCM systems to current developments such as Industry 4.0 and the Internet of Things. Most business processes are managed using an ERP system. SCM systems help one to optimize supply chains